2023
DOI: 10.3390/app13042076
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Background and Clinical Procedures in Oral Surgery Haemostasis Disorders: A Narrative Review

Abstract: Haemostasis disorders are serious pathologies that could put dental and surgical procedures at risk as they are associated with postoperative bleeding, which in some circumstances could be prolonged and dangerous for the patient. In-depth knowledge of the problems associated with coagulation pathologies and the suitable specific procedures should be implemented in dental practice. A good awareness of the clinical protocols to be used in these circumstances may help reduce operator stress and increase patient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
(246 reference statements)
0
4
0
Order By: Relevance
“…A study examining the effects of stress and positive emotions on vaccine response revealed that individuals with a positive emotional style had significantly higher levels of antibodies post-vaccination, with a p-value of 0.02 and an effect size of 0.47. This finding suggests that psychological factors can modulate the immune system's response to vaccines [16][17] .This laboratory-based evidence underscores the impactful role of psychological suggestion in modulating the immune system's response to vaccines. The observed correlation between positive emotional states and enhanced antibody production provides a tangible link between psychological factors and physiological outcomes.…”
Section: Psychological Suggestion In Immune Responsementioning
confidence: 62%
“…A study examining the effects of stress and positive emotions on vaccine response revealed that individuals with a positive emotional style had significantly higher levels of antibodies post-vaccination, with a p-value of 0.02 and an effect size of 0.47. This finding suggests that psychological factors can modulate the immune system's response to vaccines [16][17] .This laboratory-based evidence underscores the impactful role of psychological suggestion in modulating the immune system's response to vaccines. The observed correlation between positive emotional states and enhanced antibody production provides a tangible link between psychological factors and physiological outcomes.…”
Section: Psychological Suggestion In Immune Responsementioning
confidence: 62%
“…Experiencing profuse bleeding during oral surgery presents a considerable challenge, potentially impairing the operator's visibility and leading to prolonged post-operative bleeding or hematoma formation. Such conditions heighten the risk of bacterial infections [28]. Eating habits are a significantly debated factor in periodontal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Hemophilia patients (Figures 1 and 2) were treated by replacement therapy of the deficient factor associated with tranexamic acid, as widely documented in the literature. [20,[55][56][57]. The patient with VWD type 2B was treated with infusion of factor VIII e VWF [23].…”
Section: Surgical Procedures and Post-operative Carementioning
confidence: 99%